Sistem Pakar dalam Mengidentifikasi Penyakit Kandungan Menggunakan Metode Forward Chaining Berbasis Android - Gunawan, Adi; Defit, Sarjon; Sumijan, Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Maternal Mortality Rate (MMR) in Indonesia is very high, so that maternal health problems are a national problem. This problem needs to get top priority. The health of pregnant women is crucial for the growth of the fetus they contain. Pregnancy can cause a decrease in maternal resistance. This decrease will trigger the arrival of various diseases. For that we need a system that can identify uterine diseases quickly and accurately. This study aims to identify uterine diseases in pregnant women based on symptoms experienced. This identification is the initial information that is useful to support the decision to take preventative action. Data processed in this study were 20 patients. This data is sourced from the Sungai Melati City Clinic which goes to an obstetrician, Dr. Yandi Zulkarnaen, SpOG. The method used in processing data is Android-based Forward Chaining. The results of this study include the name of the disease, description of the disease, and treatment solutions. After testing and calculating the level of system accuracy, a good degree of accuracy is obtained from the system calculation results with an expert decision of 90% of the 20 test data. Based on the level of accuracy, the expert system is very precise in identifying uterine diseases quickly.